Current tools for the diagnosis, management and control of dental caries. Part I - Jara Porroa, Jackeline Jajaira (2019)
The diagnosis of dental caries is no longer like the traditional diagnosis that histologically mentioned the beginning and the end of a cavity. Diagnostic criteria and tools used in detecting caries lesions have been shown to affect decision-making for their treatment. Today, dental caries is considered a process; Therefore, in this article, new proposals are described that will help us with the diagnosis, management, and control of the said disease. The Cambra and Icdas criteria are the ones that are theoretically supported by scientific evidence of what is currently the pathology and its development, so the historical background of its development, its main characteristics are described, and options for integration into the diagnostic process are proposed. in favor of greater conservation of the dental structure.